2015
DOI: 10.11130/jei.2015.30.4.799
|View full text |Cite
|
Sign up to set email alerts
|

Banking Deregulations and Unemployment in South Asia

Abstract: The paper empirically examines the effects of banking deregulations on overall and youth unemployment rates in South Asian countries using panel data for the period 1991 to 2005. The results show that banking deregulations have decreased the youth unemployment rate in the region. The results also reveal that high consumption level, per capita income and bank credit have reduced the unemployment rate, while bank crisis and high wage rate have increased the unemployment rate in the region. The results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Hence, it is expected that a negative relationship will exist between banking system credit and unemployment rate. Muhammad, Rida and Bashir (2015), Göçer (2013), Feldman (2012), Shabbir et al (2012), Ordine and Rose (2008) and Bernanke and Blinder (1992) have all confirmed the economic theory that banking system credit has a negative relationship with unemployment rate. For the purpose of this study, the domestic credit provided by banks as a percentage of GDP is used as a measure of banking system credit.…”
Section: Banking System Creditmentioning
confidence: 60%
See 1 more Smart Citation
“…Hence, it is expected that a negative relationship will exist between banking system credit and unemployment rate. Muhammad, Rida and Bashir (2015), Göçer (2013), Feldman (2012), Shabbir et al (2012), Ordine and Rose (2008) and Bernanke and Blinder (1992) have all confirmed the economic theory that banking system credit has a negative relationship with unemployment rate. For the purpose of this study, the domestic credit provided by banks as a percentage of GDP is used as a measure of banking system credit.…”
Section: Banking System Creditmentioning
confidence: 60%
“…The estimated result revealed that rising credit has a negative effect on the unemployment rate in these countries. Using panel data for the period of 1991 to 2005 in South Asian countries, Muhammad, Rida and Bashir (2015) empirically assessed the influence of banking deregulations on overall and youth unemployment rates.…”
Section: Banking System Credit and Unemployment Rate: Theoretical And...mentioning
confidence: 99%
“…Suyunov (2022) reveals that bank financing can enhance economic growth and reduce unemployment in Uzbekistan. Furthermore, Zakaria et al (2015), employing panel data from South Asian countries from 1991 to 2005, found a positive impact of banking deregulation and bank financing on reducing unemployment. Suyunov (2022) and Zakaria et al (2015) provide evidence that banking intermediation through capital accumulation and the distribution of financing positively affects job creation, thereby reducing the unemployment rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While existing studies generally demonstrate a positive impact of bank financing on unemployment, it is necessary to note that Sipahutar (2016), Suyunov (2022), and Zakaria et al (2015) primarily focused on conventional banking. Limited evidence exists regarding the relationship between Sharia-compliant financing provided by Islamic banking and unemployment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Explanatory variables of unemployment depended onBui (2020),Ciftcioglu and Bein (2017),Kilic and Ozcan (2018),Nasir et al (2021),Sipahutar et al (2016),Zakaria et al (2015),Ernst (2019),Brendan and Alan (2018),Nyasha et al (2021),Olowu et al (2019),Ciftcioglu and Bein (2017) andCicchiello et al (2021). World Development Indicators is the secondary data source used in this study.…”
mentioning
confidence: 99%